2021
DOI: 10.1016/j.nicl.2021.102636
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related neuroanatomical differences in alcohol dependence: findings from the ENIGMA Addiction Working Group

Abstract: Highlights We tested gender differences in brain volumes of alcohol dependent vs control groups. Group differences in brain volumes emerged as gross and widespread. Group-by-gender effects emerged in selected brain regions (cerebellum, amygdala) In dependent users, greater alcohol use predicted smaller amygdala and larger cerebellum GM volume. Our results highlight the need to account for gender differences in MRI stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 76 publications
2
15
1
Order By: Relevance
“…Among substances of abuse, alcohol is most prominently used in females ( 3 , 11 ). In general, alcohol dependence has been associated with changes in brain volume in reward circuitry including the cortex, insula, and hippocampus ( 9 , 12 ).…”
Section: Alcoholmentioning
confidence: 99%
“…Among substances of abuse, alcohol is most prominently used in females ( 3 , 11 ). In general, alcohol dependence has been associated with changes in brain volume in reward circuitry including the cortex, insula, and hippocampus ( 9 , 12 ).…”
Section: Alcoholmentioning
confidence: 99%
“…Surprisingly, alcohol use alone versus non‐use did not demonstrate significant differences in volumetric decline. This finding appears at odds with a vast literature demonstrating volumetric deficits from heavy drinking both in adults 28,29,40–42 and adolescents [see 8 for a review]. For instance, prior work indicates smaller GMVs in brain regions, including the hippocampus, 43 and left frontal, temporal, and parietal cortices 44 in adolescents engaged in problem alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that, although young adult females smoked less cannabis while drinking, they experienced the same acute pharmacological and subjective effects as males 27 . Men and women with AUD showed different patterns of gray and white matter volumetric reduction 28 ; for instance, only males showed reduced amygdala size compared to controls 29 . Moreover, early initiation of cannabis use potentially resulted in more spatial working memory deficits in females than in male adolescents 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Considering that dopaminergic imbalance in the brain can be one of the determinants of high alcohol motivation [ 19 , 20 ], and synucleins may be critically involved in regulation of dopaminergic neurons [ 8 ] here we studied alterations in synucleins mRNA level in specific brain areas of adult male and female rats affected by prenatal alcohol exposure. It was of particular importance to focus on the sex-dependent alterations in gene expression which might provide more insight into the problem of sex differences in response to alcohol intake both in humans [ 21 , 22 ] and animal models of alcoholism [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%